Transnational contact and challenging global poverty: Intergroup contact intensifies (the right kind of) social identities to promote solidarity‐based collective action for those low in social dominance. (25th May 2018) - Hoskin, Rachael E.; Thomas, Emma F.; McGarty, Craig
Abstract: Intergroup contact and collective action have been identified as two important but potentially conflicting ways to improve intergroup relations. However, little research has investigated the effects of contact in promoting solidarity‐based collective action amongst advantaged group members, and nor has research considered the effects of contact in transnational (global) contexts. The current research provides a longitudinal test of the idea that contact promotes solidarity‐based collective action, because it intensifies supportive (opinion‐based) social identities amongst advantaged group members. However, rather than contact having uniformly positive effects on social identification, we propose that advantaged group members who value social hierarchy and reject egalitarianism (i.e., those high in social dominance orientation [SDO]), may be less affected by intergroup contact. We tested these claims in the novel domain of global inequality and support for people in developing countries. Participants ( N  = 265) completed measures of transnational contact (with people from developing countries), social identification, SDO, and collective action at two time‐points, one year apart. Tests of moderated mediation revealed that, as expected, contact promotes solidarity‐based collective action to support international development through (opinion‐based) social identification, but only for people low in SDO. Overall, findings contradict the notion that contact and collective action inevitably work against each other but, rather, contact can engage some advantaged group members (i.e., those low in SDO) in the plight of the disadvantaged. The current results highlight opinion‐based groups as a key mechanism for connecting the positive effects of intergroup contact and collective action for social change.